Android based vehicle tracking system / Omer Ali Abubakr Abd Elrhman … [et al.] - Abd Elrhman, Omer Ali Abubakr; Mohammed Ahmed, Asim; Mekki, Tarig Hyder; Mohammed Taha, Ghassan (Universiti Teknologi Mara Selangor, 2015)
Android, as an operating system, has provided users with great opportunity to innovate and get things done in a mobile device. This paper presents how to use the GPS technology in Android devices to complete an interactive application which can be used to monitor a fleet of vehicles and display their positions on Google Maps. By using SMS messages, this information can be transmitted to the server. It provides a telemonitoring system for distribution or transportation vehicles owned by a specific company. The whole system is made of two key parts. The first one is the client, which represents an Android application that is installed in the vehicle. During a vehicle’s motion, its location can be reported by SMS messages. The second is the server, which is a computer programme representing a map using Google Maps to show the last known locations of all tracked vehicles. The current system is able to provide the monitoring process from anywhere. The purpose of this system is to use the Android platform to provide the following features: i) Location information (longitude, latitude). ii) Real time tracking using SMS. iii) Map View of all vehicles’ locations. This system is needed by many companies to monitor illegal and unethical use of their vehicles. It also provides assurance that the location of the vehicle is known in the case of robbery.